The Effect of Water Quality Parameters on Gonad Maturity of Marble Goby (Oxyeleotris Marmorata) Fed Earthworms - Rukmini Rukmini; Adriani Adriani (Center for Journal Management and Publication, 2022)
This study aims to determine the effect of average water quality parameters on gonad maturity of Marble goby (Oxyeleotris marmorata) fed with earthworms. This research was conducted in Awang Village, East Bangkal, Banjar Regency, South Kalimantan. The data was analyzed by using regression analysis. The results of the analysis of water quality parameters, namely temperature, dissolved DO, CO2, pH, and ammonia in the research container were related to the number of Marble goby that were TKG IV in several treatments. Treatment A1B1 (30 cm water height, earthworm feed without vitamin E), A1B2 (30 cm water height, earthworm feed + vitamin E 75 mg/kg), A1B3 (30 cm water level, earthworm feed + vitamin E 85 mg /kg), A2B1 (water height 50 cm, earthworm feed without vitamin E), A2B2 (water height 50 cm, earthworm feed + vitamin E 75 mg/kg), A2B3 (water level 50 cm, earthworm feed + vitamins E 85 mg/kg). The results showed that the regression equation between the temperature of the parent TKG number IV is R 2 = 0.0172, DO with a number of parent TKG IV is R 2 = 0.2737, CO 2 by the number of parent TKG IV is R 2 = 0.0238, pH with the number of parents with TKG IV is R 2 = 0.2787, and NH 3 with the number of parents having TKG IV is R 2 = 0.0816.